Problematika Hukum Keluarga Kontemporer: Analisis Hukum Positif (UU No. 1 Tahun 1974 dan PP No. 9 Tahun 1975) - Eva Nur Hopipah; Abdullah Syafe'i (CIC Lembaga Riset dan Konsultan Sosial, 2023)
ABSTRACT The contemporary family law issues in Indonesia are numerous, especially as we enter an era where everything unfolds rapidly, impacting the stability of the family as the smallest unit in society. Ten issues analyzed in this research include: (1) marriage via teleconference and divorce over the phone, as reviewed under Law No. 1 of 1974 and Government Regulation No. 9 of 1975; (2) legal consequences of interfaith marriages; (3) joint property (gono gini) post-divorce; (4) mut'ah payments for career women; (5) divorce decisions without marriage certificates; (6) domestic violence; (7) the legality of polygamy; (8) clandestine divorces; (9) post-divorce child custody rights; (10) age restrictions on marriage. All are examined in the context of Law No. 1 of 1974 and Government Regulation No. 9 of 1975. The research aims to comprehensively address family law issues within the framework of positive law (Law No. 1 of 1974 and Government Regulation No. 9 of 1975). The research methodology involves literature review, utilizing primary sources such as Law No. 1 of 1974 and Government Regulation No. 9 of 1975, contemporary family law issues, and other sources serving as secondary references to ensure the research's comprehensiveness. ABSTRAK Problematika hukum keluarga kontemporer di Indonesia sangatlah banyak, apalagi dewasa ini memasuki era dimana segala hal bergulir dengan cepat yang berpengaruh pula pada stabilitas keluarga sebagai organisasi terkecil di masyarakat. Sepuluh problematika yang dianalisis dalam penelitian ini, di antaranya, (1) perkawinan melalui teleconference dan perceraian melalui telepon ditinjau dari UU no. 1 tahun 1974 dan PP no. 9 tahun 1975; (2) akibat hukum perkawinan beda agama; (3) harta bersama (gono gini) pasca perceraian; (4) pemberian mut’ah wanita karir; (5) putusan perceraian tanpa akta perkawinan; (6) kekerasan rumah tangga; (7) bagiamana hukum poligami; (8) perceraian di bawah tangan; (9) hak asuh anak pasca perceraian; (10) pembatasan usia perkawinan. Semuanya ditinjau dari UU no. 1 tahun 1974 dan PP no. 9 tahun 1975. Hasil dari tujuan penelitian ini diharapkan mampu menyelesaikan problematika hukum keluarga secara komprehensif ditinjau dari hukum positif (UU No. 1 tahun 1974 dan PP no. 9 tahun 1975). Metode penelitian yang digunakan adalah studi kepustakaan dengan sumber primernya adalah UU no. 1 tahun 1974 dan PP no. 9 tahun 1975, problematika hukum keluarga kontemporer, dan sumber lain yang membantu penelitian ini agar komprehensif digunakan sebagai sumber sekunder.